335 Low BRCA 1/2 germline mutation rate in a french canadian population. (13th November 2020) - Bernard, J; Mehros, W; Renaud, M; Grégoire, J; Douville, P; Sébastianelly, A; Plante, M
Abstract : Objective: Universal genetic testing has become increasingly important in the management of women with epithelial tubo-ovarian and peritoneal carcinoma. Worldwide, the reported rates of deleterious BRCA mutation rate vary between 12–15%. We wanted to evaluate the mutation rate in our population considering its specific genetic background (French Canadian ascent). Method: Mainstreaming genetic testing was implemented in our service in Mai 2017 and offered to all patients with epithelial tubo-ovarian or peritoneal carcinomas, except mucinous and borderline tumors. The data was prospectively collected in a database and retrospectively analyzed. Results: A total of 214 patients were tested in our center, 169 (79%) were high grade serous carcinomas (HGSC). Overall, 137 patients had no mutation (64%). Deleterious BRCA 1/2 mutations were observed in 10 patients (4, 7%), 4 BRCA1 and 6 BRCA2, nearly all were in HGSC (9). Other non BRCA-mutations (ATM, RAD51C, RAD51D, BRIP1, CDH1, MRE11, MSH6, MUTYH, PALB2 and PMS2) were observed in an additional 18 patients (8, 4%): 16 HGSC, 1 endometrioid and 1 carcinosarcoma. VUS were seen in 57 patients (26, 7%) of which 4 were BRCA1/2 VUS. No deleterious mutations were identified in clear cell carcinomas and seen in only one low grade serous carcinoma. Conclusion: In our specific French Canadian population, the deleterious germline BRCA mutation rate was surprisingly low (4, 7%), less than half the rate reported in the literature. Based on Health Canada's current approval, only a small proportion of our patients could access PARPi therapy. Hopefully canadian indications for PARPi will soon include non-BRCA and somatic mutations.